The Pandemic’s Extensive Reform Agenda : How Can the Development Community Contribute? - Smets, Lodewijk; Record, Richard James Lowden (Washington, DC: World Bank, 2022)
The COVID-19 crisis requires policy reforms on many fronts, from debt sustainability to climate-smart recovery. This Research & Policy brief draws on theory and empirical evidence to explore the opportunities for the international development community to support policy and institutional reform. The focus is on four dimensions of support: conditional financing, policy dialogue, analytical work, and political institutions. While budget support is important to close financing gaps, the Brief argues that high-quality analytical work and policy dialogue may be needed for sustained reform success. Although political institutions determine public policy, the Brief cautions that supporting changes in the political system may lead to unintended consequences. The Research & Policy brief concludes with a discussion and some avenues for future research in this field.